Plasma from pre‐eclamptic patients induces the expression of the anti‐angiogenic miR‐195‐5p in endothelial cells. Issue 6 (24th March 2016) - Sandrim, Valeria Cristina; Dias, Mayara Caldeira; Bovolato, Ana Lívia de Carvalho; Tanus‐Santos, Jose E; Deffune, Elenice; Cavalli, Ricardo C.
Abstract: We examined the effect of plasma incubation from preeclampsia pregnant on the antiangiogenic miR‐195‐5p expression. Higher miR‐195‐5p expression was found in cultures incubated with preeclampsia plasma compared to those incubated with healthy pregnant plasma. Next, as VEGF is a target of miR‐195‐5p we have quantified its expression by real‐time qPCR and ELISA. We found reduced VEGF levels in culture incubated with preeclampsia plasma. Therefore, we have concluded that the higher expression of miR‐195‐5p in endothelial cell cultures incubated with preeclampsia plasma may contribute to decreased expression of VEGFA (gene and protein) and increased antiangiogenic status in preeclampsia. Therefore, this miR may be an important target in preeclampsia.